Essential Health and Nutrition Service Provision during the COVID-19 Pandemic: Lessons from Select Ethiopian Woredas. Issue 4 (18th March 2021) - Workicho, Abdulhalik; Kershaw, Meghan J; Berhanu, Lioul; Kebede, Mebit; Kennedy, Eileen
ABSTRACT: The world has faced a public health emergency due to the emergence of the COVID-19 pandemic. A cross-sectional study with mixed methods was conducted to review the status of maternal and child health care and nutrition service delivery during the early months of the pandemic in woredas (districts) targeted by the Growth through Nutrition Activity, a multi-sectoral nutrition project in Ethiopia. Comparison with the previous year showed some decline in key maternal and child health and nutrition services, with more pronounced effects during the early months of March and April before coordinated effort and standard guidance were well established. A recovery of most services was likely due in no small part to a range of mitigation interventions implemented by respective health workers and institutions, supervising government organizations, and through support from non-governmental organizations. Abstract : Findings from a cross-sectional, mixed-method study reviewing status of maternal and child health and nutrition service delivery in select areas of Ethiopia during the COVID-19 pandemic.